Applications of artificial immune systems to computer security: A survey - Fernandes, Diogo A. B. (2020)
For the last two decades, artificial immune systems have been studied in various fields of knowledge. They were shown to be particularly effective tools at detecting anomalous behavior in the security domain of computer systems. This article introduces the principles of artificial immune systems and surveys several works applying such systems to computer security problems. The works herein discussed are summarized and open issues are pointed out afterwards, elaborating on a novel applicability of these systems to cloud computing environments.